Rancangan Sistem Pakar Diagnosa Penyakit Gigi Menggunakan Metode Certainty Factor dengan Model UML Berbasis Web : (Studi Kasus: Bethesda Dental Care) - Linda Rahayu; Rizal Rizal (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
An expert system is a computer program designed to imitate the decision-making ability of an expert in a particular field, combining knowledge and rules obtained from experts to diagnose problems, provide advice, or make complex decisions, especially in dental diseases, so this requires the design of an expert system application for website-based dental disease diagnosis with a UML model for users who support the diagnostic process using the certainty factor method, in terms of the explanation of the certainty factor which has a concept based on symptoms and diagnoses from the weight of an expert's value and the user's value, then calculated with the formula in CF, the final result is the creation of a website-based dental disease diagnosis expert system.